Climate, fire and vegetation history at treeline east of Hudson Bay, northern Québec. (15th February 2021) - Gajewski, Konrad; Grenier, Alain; Payette, Serge
Abstract: This study investigates the spatio-temporal postglacial development of the vegetation in the northwestern part of the forest-tundra of northern Québec, Canada. Six lake sediment cores and 59 modern sediment samples were collected in an area of 16 by 7 km and analyzed for pollen and charcoal. Following a brief herb and shrub tundra period and a period with abundant Alnus, Picea mariana grew in the region for at least the past 4000 years, but there was a gradient across the area, with Picea growing to the west but not toward the east. The period of maximum Picea abundance varied between sites, but was generally between 1500 and 2500 years ago. Neoglacial cooling resulted in a decrease in Picea on the landscape, but the timing of the decline at any site depended on removal of Picea by fire. There was a gradient in Picea abundance across this study area, which resulted in a reconstructed spatial July temperature gradient of ∼1 °C across this 16 km region. In spite of the importance of fire in affecting local Picea populations around any lake, the paleoclimate reconstructions showed a long-term neoglacial cooling of ∼1 °C over the past 3800 cal yr BP, with superimposed century-scale fluctuations of ∼0.2 °C, corresponding to the Little Ice Age, the Medieval Warm Period, the Dark Ages Cold Period and the Roman Warm Period. High-resolution pollen records can therefore be used to reconstruct not only regional vegetation and climate history, but also local differences within small areas. Highlights: Six postglacial pollen and charcoal records in a 16 × 7 km area in NW Québec. Impact of the interaction of fire and climate on the vegetation shown. Vegetation and climate gradient across this area quantified. Neoglacial cooling and century scale fluctuations recorded.